The Functional Role of Spinal Interneurons Following Traumatic Spinal Cord Injury - Zavvarian, Mohammad-Masoud; Hong, James; Fehlings, Michael G. (Frontiers in Cellular Neuroscience, 2020)
Traumatic spinal cord injury (SCI) impedes signal transmission by disrupting both the local neurons and their surrounding synaptic connections. Although the majority of SCI patients retain spared neural tissue at the injury site, they predominantly suffer from complete autonomic and sensorimotor dysfunction. While there have been significant advances in the characterization of the spared neural tissue following SCI, the functional role of injury-induced interneuronal plasticity remains elusive. In healthy individuals, spinal interneurons are responsible for relaying signals to coordinate both sympathetic and parasympathetic function. However, the spontaneous synaptic loss following injury alters these intricate interneuronal networks in the spinal cord. Here, we propose the synaptopathy hypothesis of SCI based on recent findings regarding the maladaptive role of synaptic changes amongst the interneurons. These maladaptive consequences include circuit inactivation, neuropathic pain, spasticity, and autonomic dysreflexia. Recent preclinical advances have uncovered the therapeutic potential of spinal interneurons in activating the dormant relay circuits to restore sensorimotor function. This review will survey the diverse role of spinal interneurons in SCI pathogenesis as well as treatment strategies to target spinal interneurons.